PENGARUH POLA MAKAN TERHADAP KEJADIAN STROKE HEMORAGIK DI RUANG POLIKLINIK SARAF RSUD TGK CHIK DITIRO SIGLI - Teuku Jauhardin,* Rachmat Andi Hartanto,* Endro Basuki,* Ismail Setyopranoto** (Neurona Majalah Kedokteran Neuro Sains, 2020)
INTRODUCTION INTRACEREBRAL HEMORRHAGE ACCOUNTS FOR 10 OF ALL STROKES AND IS ASSOCIATED WITH HIGH MORTALITY ACEH PROVINCE HAS A PREVALENCE OF STROKE AS MUCH AS 66 PER MILE THE DIET PATTERN OF ACEHNESE PEOPLE TENDS TO BE HIGH IN FAT AND PROTEIN BUT LOW IN FIBER CAUSES AN IMBALANCE IN NUTRIENT INTAKE A RISK FACTOR FOR HEMORRHAGIC STROKE